Evaluation of Character Education Program Based on the Cipp Model in Improving Student Discipline in Junior High Schools in Surabaya City, East Java Province - Arni, Herda; Royyan, Nur Muhammad; Arisman, Arisman; Wafir, Ahmad (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to evaluate a character education program based on the Context, Input, Process, and Product (CIPP) model in improving student discipline at the junior high school (SMP) level in Surabaya City, East Java Province. The CIPP evaluation model is used to comprehensively assess the program, starting from the implementation context, resource readiness, implementation process, to the outcomes achieved. This research employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, documentation, and questionnaires. The research subjects include school principals, teachers, students, and parents from several public and private junior high schools in Surabaya. The findings reveal that: (1) in terms of context, the character education program is supported by school policies and a conducive social environment; (2) in terms of input, adequate human resources and learning materials are available, although further training is still needed; (3) in the process phase, program implementation aligns with the initial plan, yet inconsistencies in execution are still encountered; and (4) in terms of product, there is a significant improvement in student discipline, both in adherence to school regulations and individual responsibility.This evaluation recommends strengthening the role of teachers as role models and enhancing continuous monitoring to ensure the program runs more effectively and sustainably.